( A ) $\frac{\overrightarrow{r_1} - \overrightarrow{r_2}}{|\overrightarrow{r_1} -\overrightarrow{r_2}|}= \frac{\overrightarrow{v_2} - \overrightarrow{v_1}}{|\overrightarrow{v_2} -\overrightarrow{v_1}|}$
( B ) $\overrightarrow{r_1} - \overrightarrow{r_2} = \overrightarrow{v_1} - \overrightarrow{v_2}$
( C ) $\overrightarrow{r_1} . \overrightarrow{v_1} = \overrightarrow{r_2} . \overrightarrow{v_2}$
( D ) $\overrightarrow{r_1} \times \overrightarrow{v_1} = \overrightarrow{r_2} \times \overrightarrow{v_2}$